Some Complexes of Cobalt(II), Nickel(II), Nickel(II) Copper(II) and Zinc(II) with Disubstituted Thiourea - A. Mustafa, Ihsan (Asian Journal of Chemistry, 2010)
Some new mononuclear and heterodinuclear complexes of the type ML2 and [ZnL2·M'L2] [where M = Co(II), Ni(II), Cu(II) and Zn(II); M' = Co(II), Ni(II) and Cu(II) and HL = N-(2-thiophenol) N-phenylthiourea (MPT) and N-(2-thiophenol)-N-ethylthiourea (MET)] have been synthesized. Their tentative structures have been assigned on the bases of elemental analysis, molar conductance measurements, room temperature magnetic measurements, infrared and electronic spectral data. The ligands act as monobasic bidentates giving tetracoordinated species.